Projecting terrestrial carbon sequestration of the southeastern United States in the 21st century. Issue 7 (29th July 2013) - Song, Xia; Tian, Hanqin; Xu, Xiaofeng; Hui, Dafeng; Chen, Guangsheng; Sommers, Greg; Marzen, Luke; Liu, Mingliang
Abstract : How terrestrial ecosystems respond to future environmental change in the 21st century is critically important for understanding the feedbacks of terrestrial ecosystems to global climate change. The southeastern United States (SEUS) has been one of the major regions acting as a carbon sink over the past century; yet it is unclear how its terrestrial ecosystems will respond to global environmental change in the 21st century. Applying a process‐based ecosystem model (Dynamic Land Ecosystem Model, DLEM) in combination with three projected climate change scenarios (A1B, A2, and B1 from the IPCC report) and changes in atmospheric carbon dioxide, nitrogen deposition, and ozone pollution, we examined the potential changes of carbon storage and fluxes in the terrestrial ecosystems across the SEUS during 2000–2099. Simulation results indicate that SEUS's terrestrial ecosystems will likely continue to sequester carbon in the 21st century, resulting in an increase in total carbon density (i.e., litter, vegetation biomass and soil carbon) from 13.5 kg C/m 2 in the 2000s to 16.8 kg C/m 2 in the 2090s. The terrestrial gross primary production and net primary production will probably continuously increase, while the net carbon exchange (positive indicates sink and negative indicates source) will slightly decrease. The carbon sequestration is primarily attributed to elevated atmospheric carbon dioxide and nitrogen deposition. Forests, including both deciduous and evergreen, show the largest increase in carbon storage as compared with other biomes, while cropland carbon storage shows a small decrease. The sequestered carbon will be primarily stored in vegetation for deciduous forest and in soil for evergreen forest. The central and eastern SEUS will sequester more carbon, while the western portion of the SEUS will release carbon to the atmosphere. The combined effects of climate and atmospheric changes on carbon fluxes and storage vary among climate models and climate scenarios. The largest increase in carbon storage would occur under the A1B climate scenario simulated by the NCAR climate model. Generally, the A1B scenario would result in more carbon sequestration than A2 and B1 scenarios; and the projected climate condition by the NCAR model would result in more carbon sequestration than other climate models.